2018
DOI: 10.2188/jea.je20160193
|View full text |Cite
|
Sign up to set email alerts
|

Body-Mass Index and Pancreatic Cancer Incidence: A Pooled Analysis of Nine Population-Based Cohort Studies With More Than 340,000 Japanese Subjects

Abstract: BackgroundA high body mass index (BMI) has been proposed as an important risk factor for pancreatic cancer. However, this association of BMI with pancreatic cancer risk has not been confirmed in Asian populations.MethodsWe evaluated the association between BMI (either at baseline or during early adulthood) and pancreatic cancer risk by conducting a pooled analysis of nine population-based prospective cohort studies in Japan with more than 340,000 subjects. Summary hazard ratios (HRs) were estimated by pooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
(63 reference statements)
3
32
2
Order By: Relevance
“…Cancer January 1, 2019 age 20 years), obesity was associated with an HR of 1.71 for pancreatic cancer. 15 In our previous report, which included only 98 cases of pancreatic cancer among men, we reported an approximately 2-fold increased risk of pancreatic cancer for men who were overweight or obese at adolescence. 14 In the current study, we demonstrate a Cancer January 1, 2019…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Cancer January 1, 2019 age 20 years), obesity was associated with an HR of 1.71 for pancreatic cancer. 15 In our previous report, which included only 98 cases of pancreatic cancer among men, we reported an approximately 2-fold increased risk of pancreatic cancer for men who were overweight or obese at adolescence. 14 In the current study, we demonstrate a Cancer January 1, 2019…”
Section: Discussionmentioning
confidence: 83%
“…The Cancer Prevention Study II cohort reported that, after adjusting for age, sex, smoking, BMI, and diabetes, pancreatic cancer mortality was higher among Jewish participants than among non-Jewish whites (relative risk, 1.43; 95% CI, 1.30-1.57). 15 We expect to produce more conclusive results at the next linkage of cancer cases planned in our cohort. Furthermore, the young age of the cohort at the termination of follow-up and the young mean age of the individuals may have played a role.…”
Section: Figurementioning
confidence: 80%
See 2 more Smart Citations
“…Apart from these malignancies, epidemiological evidence of the associations between body fatness at a young age and other malignancies has been accumulating within the past few decades . A number of studies have investigated the associations between body fatness at a young age and cancers of the pancreas (34)(35)(36)(37)(38)(39)(40)(41)(42)(43), renal cell (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) and thyroid (56)(57)(58)(59)(60)(61)(62), as well as DLBCL (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17); fewer studies have reported associations between body fatness at a young age and hepatocellular carcinoma (26)(27)(28)(29), multiple myeloma (12,14,(30)…”
Section: Introductionmentioning
confidence: 99%